Analyzing the Challenges to Adoption of Drones in the Logistics Sector Using the Best-Worst Method - Çıkmak, Sinan; KIRBAÇ, GÖKHAN; Kesici, Buşra (Adem Anbar, 2023)
Drones, which are unmanned aerial vehicles, are used in various areas. Some important worldwide companies have been interested to integrate drone technology into their logistics applications. Although the use of drones promises various advantages such as reducing costs and improving responsiveness in the logistics sector, there are also various challenges to the adoption of this technology. Therefore, this study aims to identify and prioritize the challenges to drone technology adoption in the logistics sector. Initially, 34 challenges under seven major dimensions for the study were identified by a thorough literature review and consultation with selected experts. Then, the best-worst method (BWM) is applied to rank these major challenges and associated sub-criteria. The results show that “terrorist attacks”, “lack of legal regulations”, “difficulty of flight permit processes”, “flight area limitation due to restrictive visual line of sight (VLOS)”, and “personal data protection” are the top five challenges that confront the logistics sector for adopting drone technology. The findings of this research will provide important insights to practitioners and researchers interested in new technologies that can be applied in the logistics sector.
Keywords: Drones; Logistics; Unmanned Aerial Vehicle; Challenge Analysis; Best- Worst Method